ANALISIS PENGARUH STRUKTUR CORPORATE GOVERNANCE TERHADAP PENERIMAAN OPINI AUDIT NON-UNQUALIFIED - Japarudin, Japarudin; Tarmizi, Achmad (Diponegoro Journal of Accounting, 2012)
This study examines the influence of corporate governance structure on audit qualification in Indonesian listed firms. Blockholder ownership, managerial ownership, board independency, audit commitee and board size are estimated to have relationship on probability of non-unqualified opinion issued by public accountant. This research also considers sales, profitability, leverage and liquidity as control variables.This study used data from financial reports of manufacturer companies listed in BEI during 2001-2010. Samples are obtained by purposive sampling judgement. Logistic regression analysis with matched pair design is purposed to test the research problems on 92 non-unqualified opinion companies and their 92 paired samples.The result of this study indicates that blockholder ownership, managerial ownership, board independency, audit commitee and board size do not have a significant impact on probability of given non-unqualified audit opinion. While sales, profitability and leverage have a significant impact on probability of given non-unqualified audit opinion.